Pengaruh Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kabupaten Karawang (Studi Komparasi Sebelum dan Sesudah Penerapan Undang Undang No.28 Tahun 2009) - HARIS ABUBAKAR SIDIK HARIS ABUBAKAR SIDIK; SYAEFUDIN AZIZ SYAEFUDIN AZIZ (POLITEKNIK PIKSI GANESHA, 2019)
The problem raised in this study is to find out and analyze the influence of Regional Taxes and Regional Levies Against the Local Revenue of Karawang Regency (Comparative Study Before and After the Implementation of Law No.28 of 2009). This research method uses desktiptif and verification methode. There are some conclusions as follows: Before the adoption of Law No. 28 of 2009 the Regional Tax, the trend tends to be fuctuative but moves positively. After the application of Law No. 28 of 2009 Regional Taxes After the application of Law No. 28 of 2009, the trend tends to be volatile or negative tendency. Before the adoption of Law No. 28 of 2009 the Regional Retribution of the trend declined or had a negative tendency. After the application of Law No. 28 of 2009, the Regional Levies tend to decline or have a negative tendency. Prior to the adoption of Law No. 28 of 2009 the Regional Original Income (PAD) trend tended to be fuctuative but it moved positively. After the application of Law No. 28 of 2009 the Regional Original Income (PAD) trend tends to be volatile or negative tendency.Partially Regional Taxes do not affect Regional Original Revenue (PAD) Before the Implementation of Law No. 28 of 2009 on the Regional Revenue Agency (BAPENDA) of Karawang Regency. The Mean Two Difference Test shows that the significance value (0.152)> (0.050). Thus the conclusion that there are significant differences in the acceptance of Regional Original Income before and after the application of Law No. 28 of 2009.